Geographic information system in factors of dengue hemorrhagic fever disease in the working area of Kasihan II health center Bantul districts - Ivan Tinarbudi Gavinov (Fakultas Kedokteran Universitas Gadjah Mada, 2019)
Background: DHF is one of the public health problems in Indonesia, DHF is an infectious disease caused by dengue virus and transmitted through the bite of the Aedes Aegypti mosquito. The highest incidence occurred in the work area of Kasihan II Health Center, Bantul Districts. In the work area of Kasihan II health center in Tirtonirmolo village and Ngestiharjo village Bantul Districts there were 29 cases of dengue in 2017.Objective: To find out the factors that affect DHF and the incidence of DHF and find out information regarding the incidence of DHF using the GIS method in the working area of the accepted Health Center II Bantul Districts.Method: This type of research is quantitative descriptive with a Case Control study with 58 samples, namely 29 cases and 29 controls for dengue cases in the work area of Kasihan II Health Center, Bantul Districts, Yogyakarta in October 2018. Analysis of the data used is quantitative analysis using Chi Square.Results: Environmental factors and community risk factors related to DHF that can increase the risk of dengue fever (DHF) and buffer maps that explain the distance of flying mosquitoes at a distance of 100 meters, 300 meters and 500 meters.Conclusion: Factors that can increase DHF containing used goods, house fences that can accommodate air, ventilation or sunlight that enter the house, respondents who have experienced DHF, transmission of DHF through neighbors or schoolmates, the habit of opening an air shelter.